Ion heating by nonlinear Landau damping of high-n toroidal Alfvén eigenmodes in ITER. (11th August 2021) - Seo, Jaemin; Na, Y.-S.; Hahm, T.S.
Abstract: Bulk ion heating from nonlinear Landau damping of high- n toroidal Alfvén eigenmodes (TAEs) excited by energetic ions is studied. Based on the nonlinear saturation level of high- n TAEs which is confirmed by numerical studies of a wave-kinetic equation incorporating the ion Compton scattering-induced spectral transfer and the particle trapping by the wave, we assess potentially beneficial effect of bulk ion heating, so-called alpha channeling for ITER DT plasmas using an integrated simulation. The result indicates that, in its optimistic limit, the anomalous ion heating due to high- n TAEs can compensate the heating reduction due to energetic particle loss.